Transcription Factor SsSte12 Was Involved in Mycelium Growth and Development in Sclerotinia sclerotiorum - Xu, Tingtao; Li, Jingtao; Yu, Baodong; Liu, Ling; Zhang, Xianghui; Liu, Jinliang; Pan, Hongyu; Zhang, Yanhua (Frontiers in Microbiology, 2018)
Sclerotinia sclerotiorum is a challenging agricultural pathogen for management, causing large global economic losses annually. The sclerotia and infection cushions are critical for its long-term survival and successful penetration on a wide spectrum of hosts. The mitogen-activated protein kinase (MAPK) cascades serve as central signaling complexes that are involved in various aspects of sclerotia development and infection. In this study, the putative downstream transcription factor of MAPK pathway, SsSte12, was analyzed in S. sclerotiorum. Silencing SsSte12 in S. sclerotiorum resulted in phenotypes of delayed vegetative growth, reduced size of sclerotia, and fewer appressoria formation. Consequently, the SsSte12 RNAi mutants showed attenuated pathogenicity on the host plants due to the defect compound appressorium. Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays demonstrated that the SsSte12 interacts with SsMcm1. However, the SsMcm1 expression is independent of the regulation of SsSte12 as revealed by qRT-PCR analysis in SsSte12 RNAi mutants. Together with high accumulation of SsSte12 transcripts in the early development of S. sclerotiorum, our results demonstrated that SsSte12 function was essential in the vegetative mycelial growth, sclerotia development, appressoria formation and penetration-dependent pathogenicity. Moreover, the SsSte12-SsMcm1 interaction might play a critical role in the regulation of the genes encoding these traits in S. sclerotiorum.